Molecularly imprinted polypyrrole counter electrode for gel-state dye-sensitized solar cells. (10th May 2019) - Sangiorgi, Nicola; Sangiorgi, Alex; Tarterini, Fabrizio; Sanson, Alessandra
Abstract: The chemical complexity of traditional Dye Sensitized Solar Cells (DSSCs) electrolyte requires the development of high selectivity and catalytic counter-electrode (CE) materials for the triiodide target molecule. In this work is reported for the first time that molecularly imprinted polypyrrole (MIP-PPy) can help to overcome these challenges. Different template molecules such as 2-aminoacetic acid (Glycine) and L-2-aminopropionic acid (l -Alanine) are considered during the electropolymerization process in order to verify the application of MIP-PPy as CE. The use of low concentration of Glycine leads to a MIP-PPy film exhibiting higher catalytic activity and electrochemical properties on triiodide reduction than the non-imprinted polypyrrole (NIP-PPy) one. Gel-state DSSCs based on MIP materials were prepared and tested and the optimized MIP-PPy CE with Glycine as template showed an increase of around 20% of the power conversion efficiency and a reduction of 50% of the charge transfer resistance in comparison with the cells based on NIP-PPy. These results demonstrate the possibility to enhance the catalytic properties of PPy CE without adding any other materials or considerable modifications of the production process but simply increasing the electrode selectivity. Graphical abstract: Image 103844